INCREASIATION ECONOMIC MANAGEMENT LITERACY FOR THE COMMUNITY THROUGH THE INDEPENDENT ENTREPRENEURSHIP PROGRAM - Witjaksana, Budi; Purwanti, Ari; Fathoni, Tamrin; Dewi, Dita Dismalasari (Universitas Pahlawan Tuanku Tambusai, 2024)
Economic management literacy is essential for empowering communities to make informed financial decisions and achieve sustainable economic growth. However, many underdeveloped communities lack access to adequate financial education and resources. The service aims to address this gap by combining financial literacy education with practical entrepreneurship training. The program utilized a Participatory Action Research (PAR) methodology, involving community members in every phase of the project to ensure that the training was relevant and tailored to their needs. The results of the program were significant. Participants demonstrated a marked improvement in their economic literacy and entrepreneurial capabilities. Many were able to develop viable business plans and initiate small-scale enterprises, leading to new economic opportunities and reduced unemployment rates within the community. The program also fostered a sense of community cohesion and mutual support, which was crucial for the sustainability of the initiatives. Additionally, participants adopted environmentally friendly business practices, contributing to long-term environmental sustainability. In conclusion, the program successfully enhanced the economic management literacy and entrepreneurial skills of community members, stimulated local economic development, and promoted sustainable practices. The success of this initiative provides a replicable model for other communities seeking to enhance their economic resilience and sustainability through integrated financial education and entrepreneurship training.